Pupils' Decisions to Pursue Technical Education - Pavelka, Jozef (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
The study presents selected results of empirical research conducted in 2019 in primary schools in Slovakia and the Czech Republic. The main goal of the research was to investigate the causes of interest/lack of interest of pupils in science, technology and studying technical subjects at secondary vocational schools. Pupils’ decisions about future studies and the influences acting on pupils in this regard are important factors that are closely related to pupils’ interest/lack of interest in science, technology and the study of technology.
Keywords: interest in technology; study of technology; primary school; research